1999
DOI: 10.1006/jcis.1998.6040
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Fouling of Ultrafiltration Membranes: Impact of Aggregate Structure and Size

Abstract: A close coupling between the structure and size of hematite flocs formed in suspension and the permeability of the cake that accumulates on ultrafiltration membranes is observed. Specific resistances of cakes formed from flocs generated under diffusion limited aggregation (DLA) conditions are at least an order of magnitude lower than cakes formed from flocs generated under reaction limited aggregation (RLA) conditions. Similar effects are observed whether the aggregation regime is controlled by salt concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
3
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(88 citation statements)
references
References 36 publications
8
76
3
1
Order By: Relevance
“…Hence, the change of inter porosity during cake layer collapse appears more significant for estimating specific resistance values than accounting for differences between intra and intra porosities within cake layers. Comparing findings with other studies, fitted porosities are higher than the reported value of ~ 0.4 for C60 nanoparticles and Bentonite colloids [76,77], and specific resistances for both of DLA and RLA are slightly higher than what is reported for aggregated nanoparticles and SiO2 colloids of 460 nm [72,77,78]. Nevertheless, specific resistances of DLA and RLA are lesser than that of Bentonite colloids of 5000 nm; this is in line with predications of equations 19 and 20.…”
Section: Resistance Predictions and Interpretationssupporting
confidence: 85%
See 2 more Smart Citations
“…Hence, the change of inter porosity during cake layer collapse appears more significant for estimating specific resistance values than accounting for differences between intra and intra porosities within cake layers. Comparing findings with other studies, fitted porosities are higher than the reported value of ~ 0.4 for C60 nanoparticles and Bentonite colloids [76,77], and specific resistances for both of DLA and RLA are slightly higher than what is reported for aggregated nanoparticles and SiO2 colloids of 460 nm [72,77,78]. Nevertheless, specific resistances of DLA and RLA are lesser than that of Bentonite colloids of 5000 nm; this is in line with predications of equations 19 and 20.…”
Section: Resistance Predictions and Interpretationssupporting
confidence: 85%
“…In addition, DLA resistance is found to be lesser than that of RLA. This is different from reports for C60 nanoparticles [76], but in agreement with others [72,[77][78][79] and equations 19 and 20.…”
Section: Resistance Predictions and Interpretationscontrasting
confidence: 63%
See 1 more Smart Citation
“…Note that this equation holds only for the instantaneous permeate concentration (ic P ) flowing out of the ultra filter and not the concentration (c P ) in the bottle collecting the permeate (see also Appendix 1). Colloidal fouling of cross-flow filtration membranes-Iron colloids are well known to cause fouling of ultrafiltration membranes (Soffer et al 2004(Soffer et al , 2002Waite et al 1999) leading to a reduction of permeate flow. In studies of Fe solubility, this also presents a problem as colloidal Fe will be adsorbed on the filter membrane and not in the retentate, resulting in an apparent loss of Fe from the system when considering a simple mass balance.…”
Section: Schlosser and Croot Fe Solubility By Cross-flow Filtrationmentioning
confidence: 99%
“…Liu, Chen, Yu, Shen and Gregory [10], in contrast, report that floc particles of a high fractal dimension as well as a large size formed by two-stage coagulant dosing mitigated TMP development more than those formed by a single dose. The strength (resistance toward shear stress) of floc particles formed by coagulation also plays an important role in the permeability of the cake layer [11][12][13]. The increase in transmembrane pressure (TMP) in an ultrafiltration (UF) system is lower with floc breakage, which lowers the fractal dimension of flocs, than without breakage [14].…”
Section: Introductionmentioning
confidence: 99%